Radość, śmiech i „dobra myśl” w literaturze staropolskiej - HANUSIEWICZ-LAVALLEE, Mirosława (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2011)
In its first part, the article briefly presents the relation between laughter and joy in medieval and early modern culture, in order to focus, in its main part, on the categories of facetudo and urbanitas, significant to Polish humanistic literature and considered by the Renaissance and Baroque writers to be an implementation of the social virtue and the “sharing of joy.” The author observes that the widespread development of such genres as the facetiae, the apothegm, the epigram, as well as the song in early modern literature grew out of the ancient culture of the convivium, a characteristic mark of which was the celebration of joy conceived of as a moral attitude and part of the ethos of the perfect gentiluomo. The author proceeds to point that in early modern Polish literature (in particular, in works of Łukasz Górnicki and Jan Kochanowski) the banquet was considered as a kind of spectacle of social joy to which the characteristic name of «good thought» (derived from Greek) was applied. The moral norms and the norms of conduct binding throughout such a spectacle referred to those of the ancient times, embracing, among others, the elimination of social divisions as well as incorporating art, which was perceived as a necessary component. In the final part of the article, the author points to the gradual disappearance of the ethos of the humanistic banquet from the Polish literature and culture of the 17th century. Translated by Dorota Chabrajska